Hubungan Faktor Risiko dengan Kejadian Malaria di Kampung Nolokla Kabupaten Jayapura - Ayomi, Ivon; Suyono, Ign. Joko; Runtuboi , Dirk Y.P. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Malaria is a dangerous disease and is still a public health problem in Indonesia, caused by parasites of the genus Plasmodium and transmitted by female mosquitoes of the genus Anopheles. The purpose of this study was to analyze the risk factors for the incidence of malaria and measured the magnitude of the various risk factors that influenced the incidence of malaria in Nolokla Village, East Sentani District, Jayapura Regency. This study used a case control study to find out how far the risk factors included the physical environment, the biological environment and the socio-cultural environment on the incidence of malaria. The case group was all people who declared clinical malaria while the control group was those who were declared free of malaria. The number of samples in this study were 60 respondents, the case samples were taken randomly as many as 30 people and the control group was also 30 people were taken by matching method. The results of the bivariate analysis showed that there were four risk factors, namely the breeding site, the condition of the walls of the house, the presence of shrubs and the presence of Anopheles larvae, and there were six risk factors that had no effect on the incidence of malaria so they were not included in the follow-up test. From the multivariate analysis, it was found that the risk factors that influenced the incidence of malaria were breeding site (p=0.035, OR=3.143, 95%CI 1.066-9.267), condition of house walls (p=0.028, OR=4.500, 95%CI=1.094-18,503), presence of shrubs (p=0.006, OR=5,000, 95%CI=1,510–16,560), presence of Anopheles larvae (p 0.028, OR=3,500, 95%CI=1.112-11.017). The most dominant risk factor that may play a role in the incidence of malaria was the presence of shrubs (Exp=3.095). Key words: malaria incidence; API; case control; Nolokla village.